The Concept of Beauty Implied in Nikāya - Amba Pali; Jayanti Endarini; Dipa Paramita Dewi; Widiyono; Tri Saputra Medhacitto; Wasiman Dhammamitto (STAB Kertarajasa, 2023)
This Tipitaka study is motivated by the many perceptions of the notion and understanding of beauty, giving rise to various beauty standards that make people attached and compete to achieve the set beauty standards. The purpose of this study is to analyze how the concept of beauty in general is and how the concept of beauty is in the Buddhist Dhamma. implied in the nikāya. Analysis of beauty in the Buddha Dhamma is found in several suttas in the nikāya. The concept of beauty is not only limited to one meaning but rather to the breadth of the diversity of concepts and understandings. The research method used is literature by collecting library materials that are coherent with the object of discussion. The collected data will be processed by: a) editing, namely re-checking the data obtained; b) organizing, namely organizing the data obtained; and c) discovery of research results, namely conducting further analysis of the results of organizing data. In addition, the writing team also used a synthesizer checklist consisting of an introduction, continuation, and ending synthetic; by considering the elements of text, context, and discourse. After carrying out these methods, the writing team will analyze the data that has been obtained so as to produce a scientific work. The results of this study show that the current beauty standards are influenced by local culture and the role of the mass media. The role of the standard of beauty is what makes people obsessed with wanting to achieve it. Meanwhile, the Buddhist view of beauty is divided into two, namely, outer beauty and inner beauty and Buddhism is not a religion that is anti-beauty. However, the Buddha taught not to be attached to the beauty that exists Keywords: Beauty, Culture, Mass Media, Buddhism about Beauty.